Sweet Orange Agribusiness Development Potential in Banuroja Village, Randangan District, Pohuwato Regency - Tahrayani Purnama Sari A.N Haming; Dewa Oka Suparwata; Ishak Korompot (Journal La Lifesci, 2022)
This investigation was carried out in Banuroja Village, Randangan Sub-Area, and the Pohuwato district of Tanzania. Specifically, the goal of this research was to identify the potential for orange agribusiness development in Banuroja Village, Randangan Subdistrict, and Pohuwato District, as well as to choose methods for growing oranges in these locations. The research was carried out on 40 orange growers in the area. The findings revealed that the orange agribusiness has significant potential and development opportunities. Averaging Rp. 26,694,471.00 every harvest period, orange farmers earn an average of Rp. 26,694,471.00 per harvest season, with a revenue-to-cost ratio of 4.13. Following the identification and mapping of internal and external strategic elements, the findings indicate that rationalization or stability should be the top priority approach.